The oxygen carrier M101 alleviates complement activation, which may be beneficial for donor organ preservation - Puissant-Lubrano, Bénédicte; Bouthemy, Charlène; Congy-Jolivet, Nicolas; Milhes, Jean; Minville, Vincent; Kamar, Nassim; Demini, Leïla; Zal, Franck; Renaudineau, Yves (Frontiers in Immunology, 2022)
During organ transplantation, ischemia/reperfusion injury and pre-formed anti-HLA antibodies are the main cause of delayed graft function and recovery through the activation of the complement system. By supplying oxygen during transplantation, M101 is suspected to avoid complement activation, however, a direct effect exerted by M101 on this pathway is unknown. This was tested by using functional assays (lymphocytotoxic crossmatch test, C3d Luminex-based assay, 50% complement hemolysis [CH50], and 50% alternative complement pathway [AP50/AH50]), and quantitative assays (C3, C3a, C4, C5, C5a, C6, C7, C8, C9 and sC5b-9). M101 interferes with the anti-HLA lymphocytotoxic crossmatch assay, and this effect is complement-dependent as M101 inhibits the classical complement pathway (CH50) in a dose-dependent and stable manner. Such inhibition was independent from a proteolytic effect (fractions C3 to C9) but related to a dose-dependent inhibition of the C3 convertase as demonstrated by exploring downstream the release of the anaphylatoxins (C3a and C5a), C3d, and sC5b-9. The C3 convertase inhibition in the presence of M101 was further demonstrated in the AP50/AH50 assay. In conclusion, the use of M101 avoids the activation of the complement pathway, which constitutes an additional advantage for this extracellular hemoglobin to preserve grafts from ischemia/reperfusion injury and preformed anti-HLA antibodies.